Compensation of voltage Sag using STATCOM - Venkatesan, Savitha; Nagarajan, Booma (International Journal of Engineering and Technology, 2018)
Due to unpredicted non-linear loads, power quality problems, a raise in the transmission system. One such problem is voltage sag. Voltage sag is caused by the non-linear load which demands reactive power, but the balanced 3F source provides required reactive power of the load with reduced voltage at the receiving end. In this paper, simulation study has been performed to reducethe voltage sag issue. A transmission system with generation source with different loading conditions is considered and study has been done. A 3F medium P model transmission line is designed with a power source of 11kV.Â  A shunt connected compensation unit called Static Synchronous Compensator (STATCOM) reduces the voltage sag in the transmission line. STATCOM provides the required reactive power demanded by the non-linear load along with the source for compensation of voltage sag. The STATCOM circuit comprises of Voltage source converter(VSC) unit and a DC source. Reactive power compensation is done by VSC unit firing angle control. The source of the STATCOM can also be from renewable energy system. This AC source is converted by a AC-DC-AC converter unit.The firing angle is controlled by the control unit which ensures the continuous and balanced power flow even under sudden change in load conditions. The simulation results depict the characteristics of the developed STATCOM.